2020
DOI: 10.1080/1478422x.2020.1815950
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of octadecylamine for the corrosion inhibition of Incoloy 800

Abstract: Indian pressurised heavy water reactors use Incoloy 800 for steam generators. The pH is maintained alkaline to check corrosion in secondary circuit by the addition of Ethanolamine (ETA). Effect of octadecylamine (ODA) for further reduction of corrosion is investigated. Incoloy was exposed to both steam and liquid phases at 200°C in an autoclave for 7 days. Concentration of ETA was kept constant at 6 ppm and that of ODA was varied from 6 ppm to 20 ppm. The film grown in liquid phase was thinner and enriched wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The N–D stretching band could not be detected either (Figure S4b). This phenomenon has been reported recently by Kuilya et al that the N–H stretching of ODA is not observed in the case of the film formed with ODA on an Incoloy 800 plate . A similar observation has also been reported recently by Ida et al for the film formed with a film forming amine product (commercially available products containing a film forming amine as the film forming substance) on a carbon steel plate .…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The N–D stretching band could not be detected either (Figure S4b). This phenomenon has been reported recently by Kuilya et al that the N–H stretching of ODA is not observed in the case of the film formed with ODA on an Incoloy 800 plate . A similar observation has also been reported recently by Ida et al for the film formed with a film forming amine product (commercially available products containing a film forming amine as the film forming substance) on a carbon steel plate .…”
Section: Resultssupporting
confidence: 85%
“…This phenomenon has been reported recently by Kuilya et al that the N−H stretching of ODA is not observed in the case of the film formed with ODA on an Incoloy 800 plate. 4 A similar observation has also been reported recently by Ida et al for the film formed with a film forming amine product (commercially available products containing a film forming amine as the film forming substance) on a carbon steel plate. 26 The disappearance of the N−H vibrational peak, as also cited and mentioned by Kailya et al, was a common phenomenon observed in the case of ODA and OLA adsorbed on Fe 3 O 4 nanoparticles by Pan et al 27 Importantly, the disappearance of the N−H band is another indicator of complexation, and Pan et al attributed their undetectability of the N−H band to complexation as well.…”
Section: ■ Results and Discussionmentioning
confidence: 77%
See 1 more Smart Citation